Islam, Muslims and the Modern State
XIV, 374 p.
Keywords: This is the most recent and up-to-date study on the state of affairs in the Muslim world at a time when Muslims, like others, are confronted with the challenges posed by a rapidly changing new world order. Some 15 countries and regions are covered in this scholarly collection. The contributors are well-informed academics and experts from 10 leading universities and institutes.